Growth Response of Three Shallot Varieties (Allium Ascalonicum L.) From True Shallot Seed Given a Combination of Phosphorus and Potassium Fertilizer in Dry Land - Ika Medayanti; Kartina Kartina; Susiyanti Susiyanti; Zahratul Milla (Jurnal Agroekoteknologi, 2022)
The research was conducted at the Experimental Garden of the Integrated Agricultural System of the Banten Province Agricultural Service at an altitude of 60 m above sea level. from July to September 2021. The design of this study using a factorial randomized block design, the first factor varieties treatment consists of 3 levels: v1 = Maserati varieties, v2 = Sanren varieties, and  v3 = Tuk Tuk varieties.  Factor fertilization treatment consists of 3 levels: p1 = 54 kg/ha P2O5 +  90 kg/ha K2O, p2 = 72 kg/ha P2O5 + 120 kg/ha K2O, and p3 = 90 kg/ha P2O5 + 150 kg/ha K2O. The results showed that there was no interaction between varieties and combinations of P and K fertilizers on all observed parameters. Varieties treatment affected the number of leaves 5 weeks after planting, leaf area, plant wet weight and plant wet weight per plot, where the sanren variety had the best value, successively 16.5 strands; 499.28 cm2; 86.90 grams and 2105.01 g. The combination of fertilizer application of 90 kg/ha P2O5 + 150 kg/ha K2O was the best for the parameters of leaf area, wet weight per plant and wet weight per plot, respectively 482.02 cm2; 82.37 grams; and 2065.61 grams.